Accelerated degradation of Al3+ doped ZnO thin films using damp heat test - Litzov, Ivan; Azimi, Seyed Hamed; Matt, Gebhard; Kubis, Peter; Stubhan, Tobias; Popov, Georgi; Brabec, Christoph (Organic Electronics, 2014)
Two different types of aluminum-doped zinc oxide (AZO) thin films were fabricated using low cost sol-gel technique. By applying damp heat testing, the optical and electrical properties of those films were investigated under the influence of accelerated degradation from moisture or moisture vapor. Complementary measurements of optical transmittance, work function, and conductivity allowed exploring the degradation of AZO thin films and the corresponding OPV devices. We found that optical properties like transmittance, absorption coefficient, and band gap are not influenced by temperature and moisture. However, an increase in the work function, and a decrease in the conductivity of AZO films were observed upon damp heat exposure indicating the formation of a barrier or depletion layer at the metal oxide semiconductor interface. © 2013 Elsevier B.V. All rights reserved.
Keywords: Aluminum-doped zinc oxide; Conductivity; Damp heat test; Work function

Assessing the accuracy of imaging techniques for defect characterization on thin film solar cells - Vetter, Andreas; Hofbeck, Bernhard; Kubis, Peter; Brabec, Christoph (42nd IEEE Photovoltaic Specialist Conference, PVSC 2015, 2015)
Imaging methods are an essential tool for improving processing of solar cells. Unfortunately, it is difficult to validate the imaging methods in detail. One focus of our work was to establish an approach by which one can assess the accuracy of the determination of the influence of defects via imaging on CIGS solar cells. The method is, however, not restricted to CIGS and should be easily transferable to other solar cell types, in particular other thin film technologies. The benefit of such a method is the possibility to validate and optimize imaging techniques and, in turn, improving tools to optimize solar cell material and processing of solar cells.
Keywords: accuracy; CIGS; defects; ILIT; imaging; performance loss; quality control

Flexible organic tandem solar modules: A story of up-scaling - Spyropoulos, Georgios; Kubis, Peter; Li, Ning; Lucera, Luca; Salvador, Michael Filipe; Baran, Derya; Machui, Florian; Ameri, Tayebeh; Voigt, Monika; Brabec, Christoph (Organic Photovoltaics XV, 2014)
The competition in the field of solar energy between Organic Photovoltaics (OPVs) and several Inorganic Photovoltaic technologies is continuously increasing to reach the ultimate purpose of energy supply from inexpensive and easily manufactured solar cell units. Solution-processed printing techniques on flexible substrates attach a tremendous opportunity to the OPVs for the accomplishment of low-cost and large area applications. Furthermore, tandem architectures came to boost up even more OPVs by increasing the photon-harvesting properties of the device. In this work, we demonstrate the road of realizing flexible organic tandem solar modules constructed by a fully roll-to-roll compatible processing. The modules exhibit an efficiency of 5.4% with geometrical fill factors beyond 80% and minimized interconnection-resistance losses. The processing involves low temperature (<70 °C), coating methods compatible with slot die coating and high speed and precision laser patterning.
Keywords: Flexible solar cells; Laser patterning; Organic solar modules; Organic tandem solar cells; Solution-processing

Flexible organic tandem solar modules with 6% efficiency: combining roll-to-roll compatible processing with high geometric fill factors - Spyropoulos, Georgios; Kubis, Peter; Li, Ning; Baran, Derya; Lucera, Luca; Salvador, Michael Filipe; Ameri, Tayebeh; Voigt, Monika; Krebs, F. C.; Brabec, Christoph (Energy and Environmental Science, 2014)
Organic solar cell technology bears the potential for high photovoltaic performance combined with truly low-cost, high-volume processing. Here we demonstrate organic tandem solar modules on flexible substrates fabricated by fully roll-to-roll compatible processing at temperatures <70 °C. By using ultrafast laser patterning we considerably reduced the “dead area” of the modules and achieved geometric fill factors beyond 90%. The modules revealed very low interconnection-resistance compared to the single tandem cells and exhibited a power conversion efficiency of up to 5.7%. Bending tests performed on the modules suggest high mechanical resilience for this type of device. Our findings inform concrete steps towards high efficiency photovoltaic applications on curved, foldable and moving surfaces.
Keywords: Fill factor; Roll to Roll; Solar module GEOBASE Subject Index: photovoltaic system; resilience; solar power; volume

Fully printed organic solar modules with bottom and top silver nanowire electrodes - Tam, Kai Cheong; Kubis, Peter; Maisch, Philipp; Brabec, Christoph; Egelhaaf, Hans-Joachim (Progress in Photovoltaics, 2021)
One of the advantages of organic photovoltaics (OPV) over other contemporary technologies is its relative ease of processing. There are, however, very few works that have realized fully printed devices, including the bottom electrode, let alone with a scalable process in a reasonable device size (>1 cm(2)). In this work, design steps and optimization processes towards fully printed OPV modules with scalable processes are demonstrated for the first time. An overview on issues related to upscaling with printed electrodes is first provided. The various issues are then addressed by a rational design process supported by measurements and calculations. Finally, a set of fully printed OPV modules are fabricated using these optimized parameters that have over 3.5-cm(2) active area with 5% efficiency. For the first time, this work has also demonstrated the process compatibility of fully printed device structures with non-fullerene acceptor systems, which enables more design opportunities for the current generation of high-performance OPV materials.
CRIS-Team WoS Importer:2021-12-31

Fully Solution-Processing Route toward Highly Transparent Polymer Solar Cells - Guo, Fei; Kubis, Peter; Stubhan, Tobias; Li, Ning; Baran, Derya; Przybilla, Thomas; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (ACS Applied Materials and Interfaces, 2014)
We report highly transparent polymer solar cells using metallic silver nanowires (AgNWs) as both the electron- and hole-collecting electrodes. The entire stack of the devices is processed from solution using a doctor blading technique. A thin layer of zinc oxide nanoparticles is introduced between photoactive layer and top AgNW electrode which plays decisive roles in device functionality: it serves as a mechanical foundation which allows the solution-deposition of top AgNWs, and more importantly it facilitates charge carriers extraction due to the better energy level alignment and the formation of ohmic contacts between the active layer/ZnO and ZnO/AgNWs. The resulting semitransparent polymer:fullerene solar cells showed a power conversion efficiency of 2.9%, which is 72% of the efficiency of an opaque reference device. Moreover, an average transmittance of 41% in the wavelength range of 400-800 nm is achieved, which is of particular interest for applications in transparent architectures.
Keywords: semitransparent polymer solar cells; fully solution processing; OPV; ITO-free

High performance ternary organic solar cells with thick active layer exceeding 11% efficiency - Gasparini, Nicola; Lucera, Luca; Salvador, Michael Filipe; Prosa, Mario; Spyropoulos, Georgios; Kubis, Peter; Egelhaaf, Hans Joachim; Brabec, Christoph; Ameri, Tayebeh (Energy and Environmental Science, 2017)
We present a novel ternary organic solar cell with uncommonly thick active layer (>300 nm), featuring thickness invariant charge carrier recomb ination and delivering 11% power conversion efficiency (PCE). The ternary blend was used to demonstrate photovoltaic modules of high technological relevance both on gla ss and flexible substrates, yielding 8.2% and 6.8% PCE, respectively.

High precision processing of flexible P3HT/PCBM modules with geometric fill factor over 95% - Kubis, Peter; Lucera, Luca; Machui, Florian; Spyropoulos, Georgios; Cordero, Johann; Frey, Alfred; Kaschta, Joachim; Voigt, Monika; Matt, Gebhard; Zeira, Eitan; Brabec, Christoph (Organic Electronics, 2014)
Flexible OPV modules, based on P3HT:PCBM as absorber layer, were manufactured with a power conversion efficiency over 3% and for a total area of 3500 mm(2) consisting of 14 in series interconnected cells. The modules utilize the excellent mechanical and the outstanding optical properties of sputtered transparent ITO-Metal-ITO (IMI) electrodes deposited on the PET foil on the one hand, and the combination of large area slot-die coating with high resolution ultrafast laser patterning on the other hand. The manufacturing of modules with outstanding performance was found to be reproducible. The right combination of innovative electrodes and smart roll-to-roll compatible processing technologies demonstrates a viable path towards high efficient industrial module technology. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Flexible transparent electrode; Flexible OPV module; Slot-die coating; Ultra-fast laser patterning; High geometric fill factor

High Q femtoREGEN™ UC laser systems for industrial microprocessing applications - Matylitsky, V. V.; Kubis, Peter; Brabec, Christoph; Au, J. Aus Der (Frontiers in Ultrafast Optics: Biomedical, Scientific, and Industrial Applications XII, 2012)
High average power, high repetition rate femtosecond lasers with μJ pulse energies are increasingly used for bio-medical and material processing applications. With the introduction of femtosecond laser systems such as the High Q femtoREGEN™ UC platform, micro-processing of solid targets with femtosecond laser pulses have obtained new perspectives for industrial applications. The unique advantage of material processing with sub-picosecond lasers is efficient, fast and localized energy deposition, which leads to high ablation efficiency and accuracy in nearly all kinds of solid materials. In this paper, we will show aspects of the design and performance of the femtoREGEN™ UC industrial laser system and give an overview of actual applications. © 2012 SPI
Keywords: Ablation; Femtosecond laser pulse; Micro-processing; Ultrafast laser

ITO-Free and Fully Solution-Processed Semitransparent Organic Solar Cells with High Fill Factors - Guo, Fei; Zhu, Xiangdong; Forberich, Karen; Krantz, Johannes; Stubhan, Tobias; Salinas Batallas, Michael; Halik, Marcus; Spallek, Stefanie; Butz, Benjamin; Spiecker, Erdmann; Ameri, Tayebeh; Li, Ning; et al. (Advanced Energy Materials, 2013)
Organic photovoltaic (OPV) solar cells that can be simply processed from solution are in the focus of the academic and industrial community because of their enormous potential to reduce cost. One big challenge in developing a fully solution-processed OPV technology is the design of a well-performing electrode system, allowing the replacement of ITO. Several solution-processed electrode systems were already discussed, but none of them could match the performance of ITO. Here, we report efficient ITO-free and fully solution-processed semitransparent inverted organic solar cells based on silver nanowire (AgNW) electrodes. To demonstrate the potential of these AgNW electrodes, they were employed as both the bottom and top electrodes. Record devices achieved fill factors as high as 63.0%, which is comparable to ITO based reference devices. These results provide important progress for fully printed organic solar cells and indicate that ITO-free, transparent as well as non-transparent organic solar cells can indeed be fully solution-processed without losses. Indium tin oxide (ITO)-free and fully solution-processed organic solar cells are demonstrated by employing AgNW as both the bottom and top electrodes, in conjunction with Al-ZnO and poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) as charge extraction layers. Devices with electrical fill factor (FF) up to 63.0% and fully retained open circuit voltage (V) are achieved, indicating that superior optoelectronic and film quality properties of the two interlayers are perfectly compatible to AgNW electrodes. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Large area slot-die coated organic solar cells on flexible substrates with non-halogenated solution formulations - Machui, Florian; Lucera, Luca; Spyropoulos, Georgios; Cordero, Johann; Ali, Abid Shaukat; Kubis, Peter; Ameri, Tayebeh; Voigt, Monika; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2014)
The transfer from lab scale to industrial application is one of the challenges for organic photovoltaics. For this, non halogenated formulations are a decisive need for the upscaling process, as are roll-to-toll (R2R) compatible methods. Devices processed with o-xylene using slot-die coating as a sheet-to-sheet technique show a reduced efficiency on a larger scale compared to lab scale solar cells. By using a mixture of high and low volatile solvents which selectively dissolve one component, the film homogeneity and the efficiency is dramatically improved. The slot-die coated active layers for solar cells processed from non-halogenated solvents show device efficiencies above 3% on flexible substrates.
Keywords: Film homogeneity; Flexible substrates; Ink formulation; Organic photovoltaics; Slot-die coating; Solvent

Nanowire Interconnects for Printed Large-Area Semitransparent Organic Photovoltaic Modules - Guo, Fei; Kubis, Peter; Przybilla, Thomas; Spiecker, Erdmann; Hollmann, Andre; Langner, Stefan; Forberich, Karen; Brabec, Christoph (Advanced Energy Materials, 2015)
Semitransparent organic photovoltaic (OPV) cells promise applications in various transparent architectures where their opaque counterparts cannot contribute. Realizing practical applications of this technology requires the manufacturing of large-area modules without significant performance loss compared to the lab-scale devices. In this work, efficient semitransparent OPV modules based on ultrafast laser patterning on both glass and flexible substrates are reported. Solution-processed metallic silver nanowires (AgNWs) are used as transparent top electrodes. The efficient low-ohmic contact of the interconnects between the top AgNWs and the bottom electrode in combination with high-precision laser beam positioning system allow to fabricate semitransparent modules with high electrical fill factor of approximate to 63% and a remarkable geometric fill factor exceeding 95%, respectively. These results represent an important progress toward upscaling of high-performance OPV modules with reduced production costs.

Patterning of OPV modules by ultra-fast laser - Kubis, Peter; Lucera, Luca; Guo, Fei; Spyropoulos, Georgios; Voigt, Monika; Brabec, Christoph (Laser Processing and Fabrication for Solar, Displays, and Optoelectronic Devices III, 2014)
A novel production process combining slot-die coating, transparent exible IMI (ITO-Metal-ITO) electrodes and ultra-fast laser ablation can be used for the realization of P3HT:PCBM based thin film exible OPV modules. The fast and precise laser ablation allows an overall efficiency over 3 % and a device geometric fill factor (GFF) over 95 %. Three functional layers can be ablated using the same wavelength only with varying the laser uence and overlap. Different OPV device architectures with multilayers utilizing various materials are challenging for ablation but can be structured by using a systematical approach.
Keywords: Exible OPV module; Laser ablation; Semitransparent OPV module; Slot-die coating; Ultra-fast laser

Patterning of organic photovoltaic modules by ultrafast laser - Kubis, Peter; Li, Ning; Stubhan, Tobias; Machui, Florian; Matt, Gebhard; Voigt, Monika; Brabec, Christoph (Progress in Photovoltaics: Research and Applications, 2015)
In this paper, we demonstrate that laser patterning of organic solar cells by ultrafast laser systems (pulse length <350 fs) is an attractive process to produce photovoltaic modules with outstanding high geometric fill factors. Moreover, in terms of precision, registration, and debris generation and in terms of keeping the damage to the underneath layers at a minimum, ultrafast laser patterning with a pulse length of few hundreds of femtoseconds turns out to yield superior results. Ablation of all three different solar cell layers (electrodes (P1 and P3) and interfaces and semiconductor (P2)) is achieved with a single wavelength simply by a precise adjustment of the laser fluence and the patterning overlap. Camera positioning allows a precise registration between the various processing steps and a reduction of the width of the overall interconnection regime to the hundreds of micrometers dimension, resulting in high geometrical fill factors of over 90% for monolithically interconnected organic solar cell modules.
Keywords: Femtosecond pulses; Laser patterning; Organic solar cells; PV module

Printing high performance reflective electrodes for organic solar cells - Krantz, Johannes; Forberich, Karen; Kubis, Peter; Machui, Florian; Min, Jie; Stubhan, Tobias; Brabec, Christoph (Organic Electronics, 2015)
In this paper we solve a long term material problem of thin film organic electronics, namely the solution processing of an opaque electrode. Solution processing of opaque metallic top electrodes typically leads to severe shunting problems. We solve this issue by reversing the electrode sequence and print a highly conductive but opaque bottom electrode from metallic precursors. Devices based on these printed bottom electrodes are compared to reference stacks based on evaporated silver. The transparent top electrode is solution processed from silver nanowire inks, which results in highly transparent electrodes with excellent conductivity. The optical, mainly reflective properties of the opaque silver electrode are investigated in comparison to screen-printed silver pastes. The outstanding smoothness of the printed Ag electrode results in high reflectivity and poly(3-hexylthiophene-2,5-diyl):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) based solar cells with η >. 2.5% and high fill factors performing on par with reference devices on evaporated silver electrode layers.
Keywords: Highly reflective electrode; Printed silver precursor ink; Solution processable electrode; Substrate architecture; Superstrate architecture

Relation of Nanostructure and Recombination Dynamics in a Low-Temperature Solution-Processed CuInS2 Nanocrystalline Solar Cell - Azimi, Seyed Hamed; Heumüller, Thomas; Gerl, Andreas; Matt, Gebhard; Kubis, Peter; Distaso, Monica; Ahmad, Rameez; Akdas, Tugce; Richter, Moses; Peukert, Wolfgang; Brabec, Christoph (Advanced Energy Materials, 2013)
The understanding and control of nanostructures with regard to transport and recombination mechanisms is of key importance in the optimization of the power conversion efficiency (PCE) of solar cells based on inorganic nanocrystals. Here, the transport properties of solution-processed solar cells are investigated using photo-CELIV (photogenerated charge carrier extraction by linearly increasing voltage) and transient photovoltage techniques; the solar cells are prepared by an in-situ formation of CuInS2 nanocrystals (CIS NCs) at the low temperature of 270 °C. Structural and morphological analyses reveal the presence of a metastable CuIn5S8 phase and a disordered morphology in the CuInS2 nanocrytalline films consisting of polycrystalline grains at the nanoscale range. Consistent with the disordered morphology of the CIS NC thin films, the CIS NC devices are characterized by a low carrier mobility. The carrier density dynamic indicates that the recombination kinetics in these devices follows the dispersive bimolecular recombination model and does not fully behave in a diffusion-controlled manner, as expected by Langevin-type recombination. The mobility–lifetime product of the charge carriers properly explains the performance of the thin (200 nm) CIS NC solar cell with a high fill-factor of 64% and a PCE of over 3.5\
Keywords: nanostructures; power; conversion; nanocrystal

Semitransparent organic photovoltaic modules with Ag nanowire top electrodes - Guo, Fei; Kubis, Peter; Przybilla, Thomas; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (International Society for Optical Engineering; 1999, 2014)
Semitransparent organic photovoltaic (OPV) cells are promising for applications in transparent architectures where their opaque counterparts are not suitable. Manufacturing of large-area modules without performance losses compared to their lab-scale devices is a key step towards practical applications of this PV technology. In this paper, we report the use of solution-processed silver nanowires as top electrodes and fabricate semitransparent OPV modules based on ultra-fast laser scribing. Through a rational choice of device architecture in combination with high-precision laser patterning, we demonstrate efficient semitransparent modules with comparable performance as compared to the reference devices.
Keywords: semitransparent organic solar cells; organic photovoltaic modules; silver nanowires; laser patterning

Solution-Processed Parallel Tandem Polymer Solar Cells Using Silver Nanowires as Intermediate Electrode - Guo, Fei; Kubis, Peter; Li, Ning; Przybilla, Thomas; Matt, Gebhard; Stubhan, Tobias; Ameri, Tayebeh; Butz, Benjamin; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Acs Nano, 2014)
Tandem architecture is the most relevant concept to overcome the efficiency limit of single-junction photovoltaic solar cells. Series-connected tandem polymer solar cells (PSCs) have advanced rapidly during the past decade. In contrast, the development of parallel-connected tandem cells is lagging far behind due to the big challenge in establishing an efficient interlayer with high transparency and high in-plane conductivity. Here, we report all-solution fabrication of parallel tandem PSCs using silver nanowires as intermediate charge collecting electrode. Through a rational interface design, a robust interlayer is established, enabling the efficient extraction and transport of electrons from subcells. The resulting parallel tandem cells exhibit high fill factors of similar to 60% and enhanced current densities which are identical to the sum of the current densities of the subcells. These results suggest that solution-processed parallel tandem configuration provides an alternative avenue toward high performance photovoltaic devices.
Keywords: parallel-tandem; polymer solar cells; solution-processed; silver nanowires

Sub-bandgap photon harvesting for organic solar cells via integrating up-conversion nanophosphors - Chen, Wei; Hou, Yi; Osvet, Andres; Guo, Fei; Kubis, Peter; Batentschuk, Miroslaw; Winter, Benjamin; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Organic Electronics, 2015)
Lanthanide-doped up-conversion nanophosphors were employed as up-conversion converters (UC-converters) combined with organic solar cells (OSCs). The optical properties of the external up-conversion layers were investigated, and the optimized layers were laminated with OSCs. Strong photocurrents were observed when OSCs with an UC converter were illuminated by a NIR laser. An improvement of photocurrent and efficiency were also observed under AM 1.5 G sun irradiation. Our investigations show a proof-of-concept that organic solar cells could utilize sub-bandgap photons via integrating up-conversion nanophosphors, which provide us a promising approach to exceed the efficiency limit of single junction organic solar cells.
Keywords: IR light harvesting; Nanophosphors; Organic photovoltaics; Up-conversion

Tailoring green formulation: Printing and upscaling of inverted organic solar cells - Voigt, Monika; Machui, Florian; Lucera, Luca; Spyropoulos, Georgios; Cordero, Johann; Kubis, Peter; Ali, Abid Shaukat; Shalan, Ahmed E.; Brabec, Christoph (39th IEEE Photovoltaic Specialists Conference, PVSC 2013, 2013)
By tailoring the solvents of active organic solar cell layers regarding their solubility (Hansen parameters), non-halogenated solvents and solvent mixtures can be used to print the active layers of organic solar cells. Similar efficiencies to other typical laboratory methods as spin-coating can be reached. Furthermore, using sheet-to-sheet printing or coating techniques compatible to mass-manufacturing and structuring by laser ablation, we can upscale to 10×20 cm and manufacture modules on plastic substrates. This is a breakthrough for organic solar cells and the next important step on the way to utilize organic solar cells for industrial manufacturing. © 2013 IEEE.
Keywords: Green solvents; P3HT:PCBM; Photovoltaic cells; Printing; Simulation; Solubility

Towards large-scale production of solution-processed organic tandem modules based on ternary composites: Design of the intermediate layer, device optimization and laser based module processing - Li, Ning; Kubis, Peter; Forberich, Karen; Ameri, Tayebeh; Krebs, Frederik C.; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2014)
We report on a novel approach including: 1. the design of an efficient intermediate layer, which facilitates the use of most high performance active materials in tandem structure and the compatibility of the tandem concept with large-scale production; 2. the concept of ternary composites based on commercially available materials, which enhances the absorption of poly(3-hexylthiophene) (P3HT) and as a result increase the PCE of the P3HT-based large-scale OPV devices; 3. laser-based module processing, which provides an excellent processing resolution and as a result can bring the power conversion efficiency (PCE) of mass-produced organic photovoltaic (OPV) devices close to the highest PCE values achieved for lab-scale solar cells through a significant increase in the geometrical fill factor. We believe that the combination of the above mentioned concepts provides a clear roadmap to push OPV towards large-scale production and commercial applications. © 2013 Elsevier B.V.
Keywords: Intermediate layer; Laser-based module processing; Optical-simulation; Organic tandem solar cells; Solution processing; Ternary composites

Visualizing the performance loss of solar cells by IR thermography - an evaluation study on CIGS with artificially induced defects - Vetter, Andreas; Babbe, Finn S.; Hofbeck, Bernhard; Kubis, Peter; Richter, Michael; Heise, Stephan J.; Ohland, Joerg; Riedel, Ingo; Brabec, Christoph (Progress in Photovoltaics: Research and Applications, 2016)
Local electric defects may result in considerable performance losses in solar cells. Infrared (IR) thermography is one important tool to detect these defects on photovoltaic modules. Qualitative interpretation of IR images has been carried out successfully, but quantitative interpretation has been hampered by the lack of “calibration” defects. The aims of this study are to (i) establish methods to induce well-defined electric defects in thin-film solar cells serving as “calibration” defects and to (ii) assess the accuracy of IR imaging methods by using these artificially induced defects. This approach paves the way for improving quality control methods based on imaging in photovoltaic. We created ohmic defects (“shunts”) by using a focused ion beam and weak diodes (“interface shunts”) by applying a femto-second laser at rather low power on copper indium gallium selenide cells. The defects can be induced precisely and reproducibly, and the severity of the defects on the electrical performance can be well adjusted by focused ion beam/laser parameters. The successive assessment of the IR measurement (ILIT-Voc) revealed that this method can predict the losses in P (maximal power extractable) with a mean error of below 10%. Copyright Â© 2016 John Wiley & Sons, Ltd.
Keywords: defects; imaging; perfomance; PV modules